Ontologias e técnicas de inteligência artificial aplicadas ao diagnóstico em fisioterapia neuropediátrica - Weinert, Luciana Vieira Castilho (2010)
This thesis proposes a new methodology based on ontologies and artificial intelligence techniques to support the diagnosis and the teaching-learning process in neuropediatric physiotherapy. In this area, standardized and objective measurements to quantify the diagnosis are difficultly found. The diagnosis is limited to inform in which months of the normal motor development a patient can be classified, based upon only on the subjective experience of the physiotherapist. In this work formal methods for knowledge acquisition and representations were used. Possible divergences of opinions between experts were systematically treated, and the acquired knowledge was represented as an ontology. Such ontology generated a set of classification rules from which three different approaches for diagnosis were developed: a crisp expert system, a fuzzy system, and another approach based on deterministic models. The crisp expert system did not accomplish to the problem. The fuzzy approach was not adequate too. The last approach was shown to be adequate for classifying a given patient with different degrees of membership to several months of the motor development. Results using this methodology suggested that it is capable of simulating objectively the diagnosis from human experts when analyzing real-world cases, in 90% of the cases. An extension of this work is the use of the developed ontology in a tool to support the teaching-learning process of neuropediatric physiotherapy. Such approach revealed fairly satisfactory. It was tested by professionals and students, and both found it promising as a multimedia educational resource. 85% strongly agreed about the ontology potential to be used as a tool for teaching-learning process. Overall, the main contributions of this thesis are: efficient knowledge management in a domain with weak standardization and high subjectivity of expert knowledge; methodologies for supporting the quantification of the diagnosis of a neuropediatric patient; and the development of an ontology-based multimedia tool for educational purposes.